1998
DOI: 10.1073/pnas.95.17.9867
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone of the oleander scale, Aspidiotus nerii : Structural characterization and absolute configuration of an unusual functionalized cyclobutane

Abstract: The sex pheromone emitted by the female oleander scale, Aspidiotus nerii (Homoptera, Diaspididae), has been isolated and characterized as (1R,2S)-cis-2-isopropenyl-1-(4-methyl-4-penten-1-yl)cyclobutaneethanol acetate by using advanced MS and NMR spectroscopic methods, as well as a variety of microderivatization sequences. The structure has been confirmed by stereo-and enantioselective synthesis of the four possible stereoisomers. The absolute configuration has been determined by comparison of the activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Grandisal 7, the oxidation product of grandisol, was found in 1983 as an aggregation pheromone component in two species of Pissodes bark weevils (22,23). Compound 8 was identified in 1998 as the sex pheromone of the oleander scale, Aspidiotus nerii (24). Compound 9 was identified in 1981 as the sex pheromone of the citrus mealybug, Planococcus citri (25), and similar structure 10 was identified as Pseudococcus cryptus sex pheromone in 2003 (26,27).…”
Section: Discussionmentioning
confidence: 98%
“…Grandisal 7, the oxidation product of grandisol, was found in 1983 as an aggregation pheromone component in two species of Pissodes bark weevils (22,23). Compound 8 was identified in 1998 as the sex pheromone of the oleander scale, Aspidiotus nerii (24). Compound 9 was identified in 1981 as the sex pheromone of the citrus mealybug, Planococcus citri (25), and similar structure 10 was identified as Pseudococcus cryptus sex pheromone in 2003 (26,27).…”
Section: Discussionmentioning
confidence: 98%
“…Although almost all female mealybug and scale insects emit chiral compounds as sex pheromone components (Bierl-Leonhardt et al 1980, Bierl-Leonhardt et al 1981, Einhorn et al 1998, Millar et al 2002, Arai et al 2003 other unnatural stereoisomers (enantiomers or diasteriomers) usually have neither inhibitory nor synergistic inßuence on the lure attraction (Dunkelblum 1999). In contrast, our Þeld test result indicated that male M. hirsutus was sensitive to the presence unnatural optical antipodes.…”
Section: Pheromone Components (R)-lavandulyl (S)-2-methylbutanoate Amentioning
confidence: 98%
“…Most known mealybug and scale insect sex pheromone esters contain an asymmetric center only in the alcoholic moiety (Bierl-Leonhardt et al 1980, 1981, Einhorn et al 1998, Millar et al 2002, Arai et al 2003, and other unnatural stereoisomers (enantiomers or diasteriomers) usually have neither inhibitory nor synergistic inßuence on insect attraction (Dunkelblum 1999). In the case of scale insects Diaspididae, two or three pheromone components are produced and each is active by itself (Dunkelblum 1999).…”
Section: Pheromone Components (R)-lavandulyl (S)-2-methylbutanoate Amentioning
confidence: 98%
“…The sex pheromone of Coccoidea has so far been identified in five species of armored scales, the family Diaspididae (Roelofs et al, 1977;Gieselmann et al, 1979a, b;Heath et al, 1979;Einhorn et al, 1998), four species of mealybug, Pseudococcidae (Bierl-Leonhardt et al, 1980, 1981Negishi et al, 1980;Hinkens et al, 2001;Arai et al, 2003;Zhang et al, 2004), and five species of the genus Matsucoccus, Margarodidae (Lanier et al, 1989;Einhorn Fig. 5.…”
Section: Comparison Of the Attraction Activity Of The Isolated Compoumentioning
confidence: 99%